2010
DOI: 10.1681/asn.2009101011
|View full text |Cite
|
Sign up to set email alerts
|

XIAP Reduces Muscle Proteolysis Induced by CKD

Abstract: X-chromosome-linked inhibitor of apoptosis protein (XIAP) is an endogenous caspase inhibitor. Caspase-3 contributes to the muscle wasting associated with chronic kidney disease (CKD) and other systemic illnesses, but whether XIAP modulates muscle wasting in CKD is unknown. Here, overexpression of XIAP in cultured skeletal muscle cells decreased protein degradation induced by serum deprivation, suggesting that caspase-mediated proteolysis contributes to muscle atrophy. We generated transgenic mice that overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…CKD was induced by 5/6 nephrectomy. 44 Initially, mice were pair fed with a weight-matched sham or a CKD mouse with 14% protein chow for 1 week and then, a high-protein diet (40% protein) for an additional 1 week. BUN is measured the rate of conversion of NADH to NAD monitored at 340 nm using the BUN Kinetic Procedure Kit (Thermo Electron, Louisville, CO).…”
Section: Animals and Ckd Modelmentioning
confidence: 99%
“…CKD was induced by 5/6 nephrectomy. 44 Initially, mice were pair fed with a weight-matched sham or a CKD mouse with 14% protein chow for 1 week and then, a high-protein diet (40% protein) for an additional 1 week. BUN is measured the rate of conversion of NADH to NAD monitored at 340 nm using the BUN Kinetic Procedure Kit (Thermo Electron, Louisville, CO).…”
Section: Animals and Ckd Modelmentioning
confidence: 99%
“…When IAP levels are reduced this leads to caspases being activated which results in apoptotic cell death. Another IAP, XChromosomelinked IAP has been shown to be red uced in the muscle of CKD mice and in vitro in muscle cells treated with serum obtained from CKD mice [46] . The activation of autophagy is known to breakdown IAPs and lead subsequently to the induction of necr optosis.…”
Section: Apoptosis and Necroptosis Crosstalkmentioning
confidence: 99%
“…Under anesthesia (pentobarbital), CKD was produced by removing the right kidney and two poles of the left kidney; hemostasis was achieved by electric cautery and pressure. 2 After surgery, CKD mice were fed 14% Protein Rodent Maintenance Diet Chow (Harlan Teklad, Madison, WI) ad libitum for 7 days before sham-operated mice were weight-matched with a CKD mouse and pair-fed a 40% protein diet for 2 weeks. 2 CKD mice with blood urea nitrogen (BUN) Ͼ100 mg/dl (Reflotron Plus Diagnostic Device; Roche Diagnostics Corporation, Indianapolis) were studied.…”
Section: Animals and Ckd Modelmentioning
confidence: 99%
“…In earlier studies of a rodent model of CKD, we found that the low muscle mass is due in part to increased protein degradation and suppressed protein synthesis. 2,3 Recently, we identified another mechanism that contributes to the development of muscle atrophy associated with CKD, namely, there are defects in the function of muscle progenitor cells (MPCs or satellite cells) that reduce their regenerative capacity. 4,5 This adverse response is relevant to muscle wasting because MPCs are required for muscle growth, the maintenance of muscle protein synthesis, and the repair of injured muscles.…”
mentioning
confidence: 99%